Quality of life in fatal disease: the flawed judgement of the social environment - Lulé, Dorothée; Ehlich, Benedikt; Lang, Dirk; Sorg, Sonja; Heimrath, Johanna; Kübler, Andrea; Birbaumer, Niels; Ludolph, Albert C. (Journal of neurology, 2013)
Decisions to prolong or shorten life in fatal diseases like amyotrophic lateral sclerosis are strongly influenced by healthy individuals, such as caregivers and physicians. Furthermore, many believe that amyotrophic lateral sclerosis (ALS) patients should decide ahead of time on advanced directives to circumvent confounding effects of subsequent cognitive impairments. The ability of healthy persons (caregivers and age-matched healthy subjects) to anticipate patients’ quality of life (QoL), depression and vital decisions was determined in a cross-sectional approach. Eighty-nine ALS patients, 86 caregivers and 102 age-matched healthy subjects were asked to judge ALS patients’ QoL and depression and the patients' wish for hastened death. Patients judged their own, the caregivers judged that of the patient under their care, healthy subjects were asked to judge that of a virtual patient. Additionally, healthy persons were asked to judge their own QoL and depression. Patients reported a satisfactory well-being and a low wish for hastened death. Healthy persons rated the patients’ QoL significantly lower and the rate of depression significantly higher. The wish for hastened death was significantly lower in the patient group compared to what healthy subjects thought the patient would wish. The assessment by others was closely related to the persons’ own well-being. Significant differences were identified between caregiver’s perspectives and the patient’s own perception of their psychological well-being. Our data suggest that caregivers and the general public significantly underestimate the QoL of ALS patients. A positive affective state can indeed be preserved in a progressive, fatal disease.